Investigating the Dose-Related Effects of Video Game Trunk Control Training in Chronic Stroke Patients With Poor Sitting Balance - Kim, Hyun Young (Ann Rehabil Med, 2018)
OBJECTIVE: To investigate the dose-related effect of trunk control training (TCT) using Trunk Stability Rehabilitation Robot Balance Trainer (TSRRBT) in chronic stroke patients with poor sitting balance. METHODS: This was a retrospective study of 38 chronic stroke patients with poor sitting balance that underwent TCT with TSRRBT. The participants were assigned either to the low-dose training (LDT) group (n=18) or to the highdose training (HDT) group (n=20). In addition to the conventional rehabilitation therapy, the LDT group received 5 sessions of TSRRBT intervention per week, whereas the HDT group received 10 sessions of TSRRBT intervention per week. The outcome measures were the scores on the Trunk Impairment Scale (TIS) and its subscales, Berg Balance Scale (BBS), Functional Ambulation Classification (FAC), and the Korean version of Modified Barthel Index (K-MBI). All outcome measures were assessed before the training and at the end of the 4-week training. RESULTS: After the 4-week intervention, TIS, BBS, FAC, and K-MBI scores showed improvement in both LDT and HDT groups. Furthermore, the improvements in TIS scores and its subscales were significantly greater in the HDT group than in the LDT group (p<0.05). CONCLUSION: TCT using TSRRBT could be an additional treatment for the conventional rehabilitation therapy of chronic stroke patients with poor sitting balance. HDT may provide more beneficial effects on improving patients’ sitting balance than LDT.